2021
DOI: 10.1007/s00402-020-03744-5
|View full text |Cite
|
Sign up to set email alerts
|

WALANT–Epinephrine injection may lead to short term, reversible episodes of critical oxygen saturation in the fingertips

Abstract: Introduction Although the WALANT technique’s long-term safeness has been demonstrated in many studies, there are only few data investigating its short-term effects on tissue perfusion and oxygen levels. It was hypothesized that, temporarily, critical levels of tissue perfusion may occur. Methods Seventeen patients, who were scheduled for different procedures in WALANT technique, were injected with 5–7 ml of 1% Articain containing 1:200,000 epinephrine at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This falls below the generally accepted maximal dose of lidocaine with epinephrine (seven mg/kg, equating to 50 mL in a 70-kg adult) [51]. Additionally, easy access to phentolamine allows for quick and efficacious reversal of any epinephrine-induced ischemia [52].…”
Section: Use Of Local Anesthesiamentioning
confidence: 84%
“…This falls below the generally accepted maximal dose of lidocaine with epinephrine (seven mg/kg, equating to 50 mL in a 70-kg adult) [51]. Additionally, easy access to phentolamine allows for quick and efficacious reversal of any epinephrine-induced ischemia [52].…”
Section: Use Of Local Anesthesiamentioning
confidence: 84%
“…When examined closely however, these studies still present findings that may be concerning when applied to at-risk populations. Several articles have found that after epinephrine injection there are changes in distal oxygen saturation [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…All levels returned to normal within 30 min but each decline had an average length of 132.5 s for a total average length of 463 s per patient. The longest patient had a total critical ischemia time of 684 s [ 14 ]. Alitinyazar et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2 While adrenaline has been shown to cause a temporary reduction in oxygen saturation in the fingertips, numerous studies have found no risk for long-term ischemia; this is supported by a large series of consecutive cases of adrenaline use in the fingers (3,110 fingers) which reported no episodes of finger ischemia. 2 5 Careful patient selection is, however, still essential, as those with peripheral vascular disease or Raynaud's disease may be at a higher risk of finger ischemia, and those with cardiac disease may suffer adverse effects from systemic absorption of local anesthetic. 6 While the novel coronavirus disease 2019 (COVID-19) pandemic caused decreased anesthetic coverage for hand surgeries, the demand for hand trauma operating remained high; WALANT has proven to be an extremely useful tool during this time.…”
mentioning
confidence: 99%